Corporate social entrepreneurship in selected South African banks. - Gonzo, Tsungai Carlene (My University, 2016)
Social entrepreneurship refers to individuals and groups using business principles to solve social problems. Corporate entities can use similar principles to bring about social change. Corporate social entrepreneurship is a strategic process designed to strengthen a business’s social initiatives. It solves social challenges in a way that creates economic benefits for the company and greater social impact. This study evaluated the way two well-established South African banking groups conducted their social investment work to determine the existence of corporate social entrepreneurship elements. It used qualitative research approaches to ascertain whether the corporate strategy created social and organisational value. It also determined the existence of corporate social entrepreneurship elements in the selected banks. The relevant data were collected using individual and focus group interviews with 12 representatives of the selected banks who contributed to the strategic and operational aspects of banks’ social outreach work. The data gathered included recent reports from 2012 and 2014. The relevant data gathered were analysed using thematic cross analysis and supplemented by content analysis based on a document review. The study found that the South African banks created social value through their social investment activities. However, the social investment activities generated limited economic value for the banks. This was attributed to specific efforts made to limit the influence of business motivations on social projects and the difficulty in attributing economic value creation to specific social interventions. Both the banks in this case study nonetheless possessed many elements of the corporate social entrepreneurship model. In conclusion, the study found that corporate social entrepreneurship elements exist in both banks. The future adoption of corporate social entrepreneurship as a deliberate strategy depends on a bank’s view on the appropriateness of gaining economic and organisational value from social activities among other factors. The banks possessed the necessary hallmarks to apply the CSE process in their strategy.
MBA Thesis
Keywords: Social responsibility of business,Social entrepreneurship,Banks and banking -- South Africa.